Continuity of GNSS as a critical attribute for safety applications in land transport - Filip, Aleš; Rispoli, Francesco (Nature Publishing Group, 2024)
The Global Navigation Satellite System (GNSS) is widely used for air traffic management-more than 150,000 aircraft and 5000 airports worldwide are equipped with SBAS (Satellite-based augmentation system) technology, which contributes to safer and more efficient air operations. The next challenge is to extend GNSS positioning to maritime, autonomous cars and railway control systems preserving their safety requirements. The main parameter is the integrity of the GNSS positioning, although the time for which the integrity is guaranteed, defined by continuity, the most demanding requirement for aviation applications, has not been sufficiently investigated for land transportation. The aim of this paper is to close this gap by clarifying: (1) where the requirement for GNSS continuity comes from, (2) why GNSS continuity is needed in land transport, and (3) how GNSS-based applications can be made more reliable when needed. Using a comparative analysis, the continuity requirements in aviation, rail, maritime, and road transport have been investigated showing their importance for railways and automotive control, paving the way to eventually update the current EN 50126 (RAMS) and ISO/TR 4804 standards respectively for railways and automated cars. One of the main findings, through Markov modeling, is the improvement of the Mean Time to System Failure (MTTFsys) that for the railway safety-of-life applications can be significantly increased from about 521 h up to 5 x 105 h. These results can contribute to accelerating the adoption of GNSS positioning for automated land transportation, by exploiting the extensive experience brought by the aviation sector where GNSS was introduced 20 years ago.
Kontinuita GNSS jako kritický atribut pro bezpečnostní aplikace v pozemní dopravě
Keywords: GNSS; continuity; reliability; mean time to failure; safety applications; train control; automated car driving.; GNSS; kontinuita; bezporuchovost; střední doba do poruchy; bezpečnostní aplikace; řízení vlaků, automatizované řízení automobilů.